2015
DOI: 10.1016/j.jval.2015.09.1431
|View full text |Cite
|
Sign up to set email alerts
|

Mapping The St George’s Respiratory Questionnaire To The Euroqol 5 Dimensions: A Study In Patients With Idiopathic Pulmonary Fibrosis

Abstract: Objectives: The Assessment of Burden of COPD (ABC) tool evaluates and visualizes the health status of patients with chronic obstructive pulmonary disease (COPD). This tool may be used during consultations to monitor the burden of COPD and to adjust treatment. The ABC tool has items in 5 dimensions: symptoms, limitations, mental status, exacerbations, and fatigue. The aim of our study was to determine the burden of each of 15 elements in the ABC questionnaire. MethOds: A discrete choice experiment (DCE) was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although this has been done in many disease conditions for the SF36, it has not been done for IPF. FREEMANTLE et al [176], however, conducted a mapping of SGRQ to the EQ5D in IPF patients, and SWIGRIS et al…”
Section: Discussionmentioning
confidence: 99%
“…Although this has been done in many disease conditions for the SF36, it has not been done for IPF. FREEMANTLE et al [176], however, conducted a mapping of SGRQ to the EQ5D in IPF patients, and SWIGRIS et al…”
Section: Discussionmentioning
confidence: 99%
“…The 36-Item Short Form Survey (SF-36) was reported in 26 studies, the EuroQol 5-level questionnaire (EQ-5D) in four studies [ 39 , 40 , 67 , 74 , 75 ], the SF-12 in two studies and one Canadian study reported Health Utilities Index Mark 2 (HUI2) scores. One study was assessing the mapping of SGRQ data to EQ-5D [ 76 ] and another study provided a mapping algorithm from SGRQ data to SF-36 [ 77 ]. Further, EQ-5D estimates from phase III trials with nintedanib in IPF (INPULSIS ® I and II) were available from an economic evaluation identified during the economic data search [ 25 ].…”
Section: Resultsmentioning
confidence: 99%